Cross-contamination: Comparison of Nasal and Chronic Leg Ulcer Staphylococcus aureus Strains Isolated from the Same Patient - Gjødsbøl, Kristine (Bentham Open, 2013)
The aim of this study was to investigate the occurrence of bacterial cross-contamination between the nasal cavity and leg ulcers. Sixteen patients were included in the study. Staphylococcus aureus was isolated from the leg ulcer of 13 patients and 6 of these patients also harboured S. aureus in the nasal cavity. Klebsiella oxytoca was found in the ulcer and the nasal cavity of one patient. PFGE analysis revealed that patients harbouring S. aureus both in the nasal cavity and the leg ulcer had the same bacterial type at both sites. None of the S. aureus isolates were methicillin resistant.